Colitis and colonic mucosal barrier dysfunction. Issue 4 (October 1995) - Gardiner, K R; Anderson, N H; Rowlands, B J; Barbul, A
Abstract : Trauma, infection, neoplasia, and inflammation can all disrupt the intact intestinal mucosal barrier to intraluminal bacteria and bacterial antigens. This study investigated the relation between colonic inflammation and colonic mucosal barrier function in three experimental models of colitis. There were significantly increased systemic endotoxin concentrations in rats with acetic acid (7.5 (1.7-119.5) pg/ml), ethanol (13.7 (0-111.2) pg/ml), and hapten induced (14.4 (5-31.1) pg/ml) colitis compared with saline controls (3.3 (0-13.7) pg/ml). Data expressed as median (range). There were significant correlations between the systemic endotoxin concentration and both the severity of colitis and of illness in acetic acid induced colitis. A significant increase in colonic permeability to 14C-polyethylene glycol was shown in rats with acetic acid (3.42 (1.36-5.63)%) and hapten induced colitis (2.86 (1.03-8.10)%) compared with saline controls (1.20 (0.67-1.36)%). Data expressed as median (range) of percentage of the intracolonic bolus excreted in urine. There was a significant positive correlation between the severity of colitis and % colonic permeability to 14C-polyethylene glycol. This and other studies provide evidence that mucosal barrier dysfunction is a feature of colitis irrespective of aetiology or species. Such barrier dysfunction may be responsible for the systemic inflammatory response and complications seen in patients with inflammatory bowel disease.